Photoactive rose bengal-based latex via RAFT emulsion polymerization-induced self-assembly. Issue 1 (28th October 2020) - Boussiron, Charlène; Le Bechec, Mickaël; Sabalot, Julia; Lacombe, Sylvie; Save, Maud
Abstract : Rose bengal shell- or core-functionalized acrylic latex synthesized by RAFT emulsion PISA: interfacial photosensitized 1 O2 production under visible light. Abstract : Copolymerization of acrylic acid (AA) with a photosensitizer-based comonomer by reversible addition fragmentation transfer (RAFT) polymerization produces a reactive stabilizer for emulsion polymerization-induced self-assembly (PISA). This polymerization in aqueous dispersed medium is a surfactant-free and solvent-free environmentally friendly process for the efficient design of dye-supported polymer colloids dispersed in water. Rose Bengal (RB) was selected as a photosensitizer for the synthesis of two types of comonomers (MRB), vinyl benzyl rose bengal (VBRB) and ethyl acrylate rose bengal (EARB). The effects of the structure of MRB and solvent for RAFT copolymerization with AA were investigated. While VBRB induced strong retardation in 1-4-dioxane, to a greater extent compared to EARB, such retardation was overcome in polar dimethyl sulfoxide. The high level of chain end fidelity of PAA-based macromolecular chain transfer agent, as highlighted by UV-visible spectroscopy and proton NMR spectroscopy, allowed for efficient chain extension. Self-assembled amphiphilic block copolymers synthesized by RAFT-mediated emulsion polymerization were stable, monodisperse core–shell particles of 90–100 nm diameter. The shell is a hydrophilic poly(ammonium acrylate- co -MRB) statistical copolymer and the core is a film-forming poly(alkyl acrylate) of poly( n -butyl acrylate), poly(ethyl acrylate) or poly( n -butyl acrylate- co -ethyl acrylate). A second synthetic route is proposed to label the particle core with a photosensitizer. Interfacial singlet oxygen production was monitored by the degradation of furfuryl alcohol quencher under visible light irradiation. The average quantum yield of supported rose bengal ( ϕ Δ = 0.64 ± 0.10) in a similar range to that of free rose bengal in water ( ϕ Δ = 0.76 ± 0.10) proves the photoactivity of photosensitizer-grafted waterborne latexes.